The work experience of male nursing teachers in Chinese universities: a phenomenological study - He, Zhenhua; Yao, Jia; De Ala, Minerva B.; Zhang, Xiaolan (Frontiers in Psychology, 2023)
Background With the increase in the number of male nursing staff, more and more highly educated male nursing staff are joining the nursing higher education industry. Nevertheless, male nursing teachers in China are still a very small group in the education industry, but they have made important contributions to nursing education in China. Work experience is a key factor in the stability of the professional team and the quality of education. However, there is little research on the professional feelings of Chinese male nursing teachers. Objective Explore the true feelings of male nursing teachers in Chinese universities about their work, understand their actual work difficulties, their sources of work stress and methods of coping with stress under the Chinese cultural background, and combine their professional expectations to provide ways to solve these problems, and help male nursing educators better apply nursing education work. Methods This study uses an interpretive and exploratory qualitative research design method, in which the participants of male nursing teachers are selected from 30 universities with nursing majors in Zhejiang Province by the method of purpose sampling, and semi-structured in-depth interviews were used to collect data. A Van Manen process was used for data analysis. The 10th respondents were saturated. Results Five themes were extracted in this study, namely realistic difficulties of career, positive feelings of career, sources of occupational stress, coping methods for occupational stress, and career development expectations. Conclusions Male nursing teachers in universities can actively adjust their thoughts and behaviors and face negative professional feelings due to gender factors. But they still need more comprehension and support from educational institutions and society. The support of leaders and universities can help them better adjust to professional development and maintain a rational and stable nursing teacher team.